ISOLATED EXTERNAL ILIAC ARTERY DISSECTION - Mário Moreira; Mafalda Correia; Joana Moreira; Luís Antunes; Manuel Fonseca (Angiologia e Cirurgia Vascular, 2020)
Spontaneous and isolated dissection of external iliac artery is very rare. The natural course of this condition is not well established. The authors report a case of a 54 year old male, military, with ankylosing spondylitis presenting with limb claudication secondary to isolated dissection of external iliac artery. Dissection was successfully managed by percutaneous stent placement.